Height control of UAV using off-board system - Ee, Tiam Boon (2013)
Many autonomous functionalities of a quadcopter require the use of a ground station, and hence they are developed off-board. On the other hand, the Autonomous Stabilization System of a quadcopter is often implemented on a custom On-board controller. This project looks into the possibility of developing this system off-board, so as to achieve the ultimate goal of integrating all autonomous functionalities into one system running on a ground station.